GAMBARAN PERSIAPAN CALON PENDONOR DARAH BAGI IBU HAMIL - Dhiva Biancha Salsabhila; Tri Sunarsih; Yuli Astuti (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
In 2018, the number of maternal deaths in the Special Region of Yogyakarta increased from 2017 to 36 cases, and in 2019 the number of maternal deaths was also at the same rate as the previous year. Therefore, the government has launched an effort to reduce MMR, namely the Delivery Planning and Complications Prevention Program (P4K). P4K indicators include birth attendants, birth attendants, place of delivery, transportation, and prospective blood donors. The purpose of this scientific papers to find out the description of the characteristics of prospective donors for pregnant women at Kasihan 1 Health Center. This study uses a quantitative descriptive method. The population consists of 204 pregnant women and the samples are 67 pregnant women selected by using slovin formula. The data analysis used in this study is univariate analysis. The results showed that there were 67 pregnant women with the results that 58 pregnant women (86,6%) had not prepared prospective blood donors, and 9 pregnant women (13,4%) had prepared prospective blood donors. The 9 porspective donors, there were 5 prospective donors (55,6%) who passed the initial selection and 4 prospective donors (44,4%) who did not pass the initial selection.